PENDEKATAN BELAJAR DAN PEMBELAJARAN - Muhammad Amir (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
This topic gives information for many approaches in learning process, and those can be developed by the teacher in classroom that make students learn refreshing and happiness. The successful of learning is seen output of students passed exam and many students clever. These approaches in this writing are: (1) individual approach, (2) group approach, (3) variation approach, (4) education approach, (5) experience approach, (6) habite approach, (7) emotional approach, (8) rational approach, and (9) fangtion approach. Then these approaches are explained specifily.